A comparative framework for culturally differentiated digital game-based learning. Issue 3 (8th August 2016) - Park, Jae; Wen, Run
Abstract : Purpose: – The purpose of this paper is to explore culture as the unit of analysis in comparative education in the context of technology-mediated learning known as digital game-based learning (DGBL). Design/methodology/approach: – Two digital games for Chinese language learning were purposefully designed and produced following existing studies in cross-cultural psychology, learning theories and second language acquisition. To corroborate the assumption that culture affects user's preference of DGBL learning interface, the two newly developed instructional tools were evaluated with eastern and western learners to find out their perceptions and choices through direct observation, pre-/post-assessments and a group interview. Findings: – The evaluation indicates the validity of the key assumptions in the theoretical framework: eastern learners were fond of the type of digital game that involves social cues and situational factors, whereas, western learners preferred a simple design and goal-oriented learning game in which they had the power of control. Originality/value: – This paper suggests a theoretical and technical framework to design, and produce culturally sensitive DGBL learning tools. Extant studies on the relationship between culture and DGBL are usually on how digital games generate unique learning experiences and culture. Looking at the same phenomenon but in a reverse direction, this study reports on how learners' culture determines their preferences in DGBL.